The Response of Tomato Fruit Cuticle Membranes Against Heat and Light - Benítez, José J.; González Moreno, Ana; Guzmán-Puyol, Susana; Heredia-Guerrero, José A.; Heredia, Antonio; Domínguez, Eva (Frontiers in Plant Science, 2022)
Two important biophysical properties, the thermal and UV-vis screening capacity, of isolated tomato fruit cuticles have been studied by differential scanning calorimetry (DSC) and UV-Vis spectroscopy, respectively. A first order melting, corresponding to waxes, and a second order glass transition (Tg) thermal events have been observed. The glass transition was less defined and displaced towards higher temperatures along the fruit ripening. In immature and mature green fruits, the cuticle was always in the viscous and more fluid state but, in ripe fruits, daily and seasonal temperature fluctuations may cause the transition between the glassy and viscous states altering the mass transfer between the epidermal plant cells and the environment. Cuticle dewaxing reduced the Tg value, as derived from their role as fillers. Tg reduction was more intense after polysaccharide removal due to their highly interwoven distribution within the cutin matrix that restricts the chain mobility. Such effect was amplified by the presence of phenolic compounds in ripe cuticles. The structural rigidity induced by phenolics in tomato cuticles was directly reflected in their mechanical elastic modulus. The heat capacity (Cprev) of cuticles was found to depend on the developmental stage of the fruits and was higher in immature and green stages. The average Cprev value was above the one of air, which confers heat regulation capacity to cuticles. Cuticles screened the UV-B light by 99% irrespectively the developmental stage of the fruit. As intra and epicuticular waxes contributed very little to the UV screening, this protection capacity is attributed to the absorption by cinnamic acid derivatives. However, the blocking capacity towards UV-A is mainly due to the cuticle thickness increment during growth and to the absorption by flavone chalconaringenin accumulated during ripening. The build-up of phenolic compounds was found to be an efficient mechanism to regulate both the thermal and UV screening properties of cuticles.